Regional aspects of long-term public sector psychiatric care in the Eastern Cape - Kiran Sukeri (South African Journal of Psychiatry, 2017)
Objectives: The objective of this research was to determine regional aspects (such as clinical, geographic and socio-demographic) influencing the use of public sector long-term psychiatric services in the Eastern Cape. This is important in improving service delivery, to assist policy developers with evidence-based research and in providing equitable and efficient resource utilisation.